Physiological gait test: an effective method for analyzing balance, locomotion, and neuromuscular disorders in rats and a comparison to the elevated beam test - Pantaleon, Lorena; Fukushima, André; Moreira, Natália; De-Paula, Leonardo Ribeiro; Ribeiro, Guilherme; Peña-Muñoz, Juliana Weckx; Faria, Beatriz do Prado Pacca; Mendonça, Marcelo; Abreu, Gabriel Ramos de; Zacarelli-Magalhães, Júlia; Delorenzi, Jan Carlo Bertassoni; Waziry, Paula A. Faria; et al. (Brazilian Journal of Veterinary Research and Animal Science, 2023)
The evaluation of animal locomotor activity is a behavioral tool widely used to measure the mechanisms underlying a particular disease, disorder, or injury, as well as the effects of exposure to a xenobiotic. The elevated beam test is one of the most used tests in rodents to assess balance and motor coordination. Despite being inexpensive and utilizing a simple apparatus, the high beam test requires a long period of animal training and habituation. The development and characterization of an alternative test, namely the gait test, has the potential to circumvent the time and effort required for animal training, deeming it an effective, inexpensive, and fast method for the analysis of behaviors that are comparably assessed by the high beam test. Therefore, the present study focused on determining the effectiveness and feasibility of the gait test for assessing rodent locomotion and balance as a replacement for the elevated beam test. For this purpose, male rats were divided into three groups: one control group exposed to a saline solution (NaCl 0.9%) and two experimental groups exposed to a single dose of either 0.2 or 1.0 mg/kg of ivermectin intraperitoneally for induction of locomotor disturbance. The high beam and gait tests were performed 15 min and 24 h after drug administration. Results show that the experimental groups had difficulty performing the tasks of either test at both time points analyzed compared to the control groups. At the high beam, experimental animals had trouble maintaining balance and walking. At the gait test, experimental animals showed alterations in gait, which were quantitated by: (a) shortening of step length, (b) decrease of stride, (c) altered step symmetry, and (d) altered stride area. Such results are indicative of compensatory efforts and were comparable between both tests. Altogether, the data indicate that the gait test meets all requirements for assessing motor coordination in rodents. The gait test is therefore validated as a complement to the elevated beam test for the study and analysis of neurodegenerative impairment and other disorders involving neuromuscular disturbances.